KERUKUNAN DAN HORMAT DALAM ETIKA JAWA - Tukan, Matius (Jurnal Euntes, 2023)
Javanese ethics is a combination of customs, worldview, values, and philosophy that is still very strong in Javanese society. Javanese ethics encompasses a moral life, where there is a conscience, and a sense of taste. Javanese ethics emphasises harmony that can be born from a process of acting in harmony and respect. The principle of harmony aims to maintain society in a state of harmony. Javanese pretence, “ethok-ethok”, is a technique that aims to maintain harmony even though feelings to the contrary are hidden. Harmony can also be achieved through the principle of respect, by speaking and carrying oneself always showing respect according to degree and position. Through the qualitative method, the author found an analysis that ethok-ethok action is teleological ethics, lying so that others are not angry.